The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1007/s102380200009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of epidermal growth factor on vascular endothelial growth factor secretion by endometrial stromal cells

Abstract: Endometrial stromal cells undergo morphological and functional changes to facilitate oocyte implantation under regulation of various hormones and growth factors. We studied physiological induction by epidermal growth factor (EGF) of vascular endothelial growth factor (VEGF) in these cells. In human endometrial stromal cells, the effect of EGF, genistein, tryphostin AG1478 (a tyrosine kinase inhibitor), and wortmannin (a phosphatidylinositol 3-kinase inhibitor) on production of VEGF was examined. Total RNA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…EGF has been shown to increase VEGF production in human endometrial stromal cells (14). Involvement of EGF in the angiogenetic cascade was also suggested by the ability of EGF to induce thrombospondin-1 and plasminogen activator inhibitor-1 (53).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…EGF has been shown to increase VEGF production in human endometrial stromal cells (14). Involvement of EGF in the angiogenetic cascade was also suggested by the ability of EGF to induce thrombospondin-1 and plasminogen activator inhibitor-1 (53).…”
Section: Discussionmentioning
confidence: 97%
“…That these factors may also modulate VEGF production is suggested by circumstantial evidence. For instance, it has recently been reported that VEGF secretion increased upon stimulation of primary cultures of papillary thyroid carcinoma as well as cell lines of leiomyosarcoma and breast cancer with hepatocyte growth factor (HGF), and that epidermal growth factor (EGF) induced VEGF production in human endometrial cells (12)(13)(14). In addition, TGF-␤ has been associated with VEGF expression and microvessel density in colorectal cancer (15).…”
mentioning
confidence: 98%
“…These findings suggest that the production of VEGF may be regulated by other mechanism involving via tyrosine kinase with IGF-I receptor to PI 3-kinase. We have previously reported that VEGF is regulated involving PI 3-kinase in human endometrium [21]. We demonstrated that PI 3-kinase might be another important pathway to modulate the production of VEGF in the amnion.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have demonstrated the production of VEGF by several organs of the reproductive system including the ovaries [17], endometrium of the uterus [18][19][20][21], and placenta [15,22]. VEGF is expressed in the trophoblast throughout pregnancy, as has been verified by immunohistochemical study [23][24][25].…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have demonstrated the production of VEGF by several organs in the reproductive system, including the ovaries (29), endometrium of the uterus (27,28,30,31), and placenta (7,32,33). Female reproductive tissues, especially the endometria of menstruating primates, show an exceptional degree of angiogenesis accompanying the monthly cycle.…”
Section: Discussionmentioning
confidence: 99%